Human Rights: Legal Measures for Expressing Racism and Racial Discrimination in Thailand Offense - Wongriantong, Thatchapong; Dechraksa, Kasama (Journal of Multidisciplinary in Humanities and Social Sciences, 2022)
The act of racial discrimination has caused violence between people and led to national losses, and the act of racism has affected human livelihood and honor. To solve the problems. The United Nations has promised to protect and prevent discrimination. They have legislated that any person violating the law will be punished with a criminal penalty. But Thailand does not have any laws or measures to control this act of racial discrimination. Therefore, should set the rules for controlling any person to prevent the act of racial discrimination. In this article, issues and impacts on racial discrimination and human rights law principles will be presented. Related to including the principles of Thai and foreign laws to lead to further amendments to the law.